A liquid chromatography–tandem mass spectrometry approach for study the tissue distributions of five components of crude and salt‐processed Radix Achyranthes in rats. (30th January 2019) - Tao, Yi; Yan, Jizhong; Cai, Baochang
Abstract: This study developed a robust and reliable approach using liquid chromatography– tandem mass spectrometry for the simultaneous determination of five saponins in rat tissues: β ‐ecdysterone, chikusetsusaponin IV, ginsenoside Ro, 25 S ‐inokosterone and chikusetsusaponin IVa. This is the first report on a comparative tissue distribution study of crude and salt‐processed Radix Achyranthes in rats. After one‐step protein precipitation by acetonitrile, the tissue samples were sent to LC–MS/MS for multiple reaction monitoring. The retention times of the five saponins and internal standard were 1.77, 3.14, 3.01, 1.83, 3.26 and 4.77 min. The standard curves showed good linear regression ( r 2  > 0.9991) in the range of 10.3–1562.5 ng/mL. The intra‐ and inter‐day accuracy and precision were within 15% of the nominal concentration. The recoveries of the five saponins were 92.0–99.9%. Finally, this approach was successfully applied to tissue distribution analysis of the five saponins after oral administration of crude and salt‐processed Radix Achyranthes in rats. The largest concentration of the five saponins was observed in kidney after salt‐processing, which indicated that processing could enhance the bioavailability.